Impact of adrenocorticotropic hormone stimulation during adrenal venous sampling on outcomes of primary aldosteronism. Issue 5 (May 2019) - Takeda, Yoshiyu; Umakoshi, Hironobu; Takeda, Yoshimichi; Yoneda, Takashi; Kurihara, Isao; Katabami, Takuyuki; Ichijo, Takamasa; Wada, Norio; Yoshimoto, Takanobu; Ogawa, Yoshihiro; Kawashima, Junji; Sone, Masakatsu; et al.
Abstract : Background: Adrenal venous sampling (AVS) is essential for identifying a surgically curable form of primary aldosteronism. Adrenocorticotropic hormone (ACTH) infusion or bolus has been reported to improve the success rate of AVS, although the effects on lateralization and its outcomes in unilateral primary aldosteronism are unclear. Methods: The success rate and lateralization indices were examined in a cohort of 2197 Japanese patients with primary aldosteronism from 28 centres who underwent AVS. Outcomes were analysed in 267 patients with aldosterone-producing adenomas (APAs). Results: ACTH loading during AVS improved the success rate from 67 to 89%, while lateralization indices decreased from 62 to 28%. Bolus, bolus along with continuous infusion or continuous infusion of ACTH did not affect both indices. The absence of clinical success (i.e. unchanged or increased blood pressure) was 33% and absence of biochemical success (persistent hypokalaemia or persistently raised aldosterone-to-renin ratio, or both) was 15%. The clinical and biochemical success rates did not differ between the three groups [lateralization index >2 in basal condition (LIb) and lateralization index >4 after ACTH loading (lateralization indices), and LIb >2 + lateralization indices<4, LIb<2+lateralization indices>4]. The three groups (LIb>4+lateralization indices>4, LIb>4+lateralization indices<4 and LIb<4+lateralization indices>4) did not show any significant differences of clinical and biochemical outcome. Conclusion: ACTH loading during AVS improved the success rate but decreased laterality. ACTH did not affect the clinical and biochemical outcomes in APA patients. These data showed that the use of ACTH during AVS was helpful for improving the success rate, but did not contribute to better outcomes.